2011
DOI: 10.1210/jc.2010-2819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Once-Weekly Sustained-Release Growth Hormone: A Double-Blind, Placebo-Controlled Study in Adult Growth Hormone Deficiency

Abstract: Weekly GH replacement with the sustained-release preparation LB03002 in adults significantly reduced FM over 6 months and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…In recent years, safety and efficacy of several sustained-release GH formulations with once a week administration have been evaluated [36,37]. Hence, preparation of long-acting GH formulations can offer a significant improvement in adherence [38].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, safety and efficacy of several sustained-release GH formulations with once a week administration have been evaluated [36,37]. Hence, preparation of long-acting GH formulations can offer a significant improvement in adherence [38].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of daily variations in GH levels when long acting preparations are administered has been speculated to result in supraphysiological IGF-I levels, which theoretically could increase the risk of malignancies and of an adverse metabolic profile. However, in the studies performed until now similar IGF-I levels and no major negative effects on glucose metabolism have been observed [46,47,50]. In this context it is probably also important to realise that once daily injections of GH are not physiological either.…”
Section: New Perspectivesmentioning
confidence: 92%
“…The pharmacokinetic and pharmacodynamic profile of LB03002 has been established in both children and adults with GH deficiency (GHD) (6,7). Preliminary efficacy and safety results from studies on GH-deficient children and adults have shown LB03002 to be a suitable candidate for long-term replacement therapy in patients with GHD (8,9). In this study, the primary objective was to evaluate the longterm efficacy and safety of LB3002 compared with daily rhGH treatment for 12 months.…”
Section: Introductionmentioning
confidence: 99%